The Internet as a Context: Exploring Its Impacts on National Identity in 36 Countries. (December 2019) - Lu, Jia; Yu, Xin
The rise of the Internet brings up a debate about its role in eroding or strengthening national identity. Taking the perspective of media ecology, this article saw the Internet as a context and explored its impacts on social context in which national identity is constructed. Using the data from the World Values Survey (2010–2014), this article carried out multilevel analyses with 50, 240 respondents in 36 countries. The results illustrate how online distribution of information, power, and freedom affects cognition, affection, and action of national identity. National identity is eroded by information distribution but is strengthened by power distribution. Power distribution and freedom distribution work together to neutralize and regulate the effects of information distribution.